Bi-articular Knee-Ankle-Foot Exoskeleton Produces Higher Metabolic Cost Reduction than Weight-Matched Mono-articular Exoskeleton - Malcolm, Philippe; Galle, Samuel; Derave, Wim; De Clercq, Dirk (Frontiers in Neuroscience, 2018)
The bi-articular m. gastrocnemius and the mono-articular m. soleus have different and complementary functions during walking. Several groups are starting to use these biological functions as inspiration to design prostheses with bi-articular actuation components to replace the function of the m. gastrocnemius. Simulation studies indicate that a bi-articular configuration and spring that mimic the m. gastrocnemius could be beneficial for orthoses or exoskeletons. Our aim was to test the effect of a bi-articular and spring configuration that mimics the m. gastrocnemius and compare this to a no-spring and mono-articular configuration. We tested 9 participants during walking with knee-ankle-foot exoskeletons with dorsally mounted pneumatic muscle actuators. In the bi-articular plus spring condition the pneumatic muscles were attached to the thigh segment with an elastic cord. In the bi-articular no-spring condition the pneumatic muscles were also attached to the thigh segment but with a non-elastic cord. In the mono-articular condition the pneumatic muscles were attached to the shank segment. We found the highest reduction in metabolic cost of 13% compared to walking with the exoskeleton powered-off in the bi-articular plus spring condition. Possible explanations for this could be that the exoskeleton delivered the highest total positive work in this condition at the ankle and the knee and provided more assistance during the isometric phase of the biological plantarflexors. As expected we found that the bi-articular conditions reduced m. gastrocnemius EMG more than the mono-articular condition. We did not find that the mono-articular condition reduces the m. soleus EMG more than the bi-articular conditions. Knowledge of specific effects of different exoskeleton configurations on metabolic cost and muscle activation could be useful for providing customized assistance for specific gait impairments.